Reconstructing past variations in environmental conditions and paleoproductivity over the last ∼ 8000 years off north-central Chile (30° S) - Munoz, Praxedes; Rebolledo, Lorena; Dezileau, Laurent; Maldonado, Antonio; Mayr, Christoph; Cardenas, Paola; Lange, Carina B.; Lalangui, Katherine; Sanchez, Gloria; Salamanca, Marco; Araya, Karen; Jara, Ignacio; et al. (My University, 2020)
The aim of this project was to establish past variations in the main oceanographic and climatic features of a transitional semiarid ecosystem on the north-central Chilean coast. We analyzed recent sedimentary records retrieved from two bays, Guanaqueros and Tongoy (30 degrees S), for geochemical and biological analyses, including the following: sensitive redox trace elements, biogenic opal, total organic carbon (TOC), diatoms and stable isotopes of organic carbon and nitrogen. Three remarkable periods were established with different environmental conditions and productivities: (1) > 6600 cal BP, (2) 4500-1800 cal BP and (3) 140 cal BP to the present (2015 CE). The first period was characterized by a remarkably higher productivity (higher diatom abundances and opal) in which large fluxes of organic compounds were also inferred from the accumulation of elements, such as Ba, Ca, Ni, Cd and P, in the sediments. Meanwhile, significantly reduced conditions at the bottom of the bays were suggested based on the large accumulation of Mo, Re and U, showing a peak at 6600 cal BP, when sulfidic conditions could have been present. According to the pollen moisture index (PMI), this was also identified as the driest interval. These conditions should be associated with an intensification of the Southern Pacific Subtropical Anticyclone (SPSA) and stronger southerly western winds, emulating La Nina-like conditions, as has been described for the SE Pacific during the early Holocene and part of the mid-Holocene. During most of the second period, lower productivity was observed; however, a small increase was identified between 3400 and 4000 cal BP, although lower amounts of diatom (valves g(-1)) and nutrient-type metal accumulations were evident. Anoxic conditions at the bottom of the bays changed to an almost stable suboxic condition during this time interval. The third period was marked by intense oxygenation after 1800 cal BP, as observed by a drastic change in the accumulation of U, Mo and Re. This was followed by a return to more reduced conditions over the past 2 centuries, characterized by a small productivity rise after similar to 140 cal BP, as suggested by the opal accumulations. Overall, lower primary productivity, lower reduced conditions at the bottom and higher-humidity conditions were established after 6600 cal BP to the present. We suggest that the oxygenation might be associated with a weak effect from the oxygen minimum zone over the shelf and intensified El Nino activity, introducing oxygenated waters to the coastal zones through the propagation of equatorial waves and establishment of conditions that reduced the primary productivity from the mid-Holocene toward the beginning of the modern era.
Keywords: Holocene climatic optimum; Environmental change